The Early Reception of Berkeley’s Immaterialism 1710–1733 - Bracken, Harry M. author. aut Link
124 p. 1 illus.
Keywords: By the time of Immanuel Kant, Berkeley had been caIled, among other things, a sceptic, an atheist, a solipsist, and an idealist. In our own day, however, the suggestion has been ad vanced that Berkeley is bett er understood if interpreted as a realist and man of common sense. Regardless of whether in the end one decides to treat hirn as a subjective idealist or as a re alist, I think it has become appropriate to inquire how Berkeley's own contemporaries viewed his philosophy. Heretofore the gen erally accepted account has been that they ignored hirn, roughly from the time he published the Principles 01 Human Knowledge until1733 when Andrew Baxter's criticism appeared. The aim of the present study is to correct that account as weIl as to give some indication not only of the extent, but more important, the role and character of several of the earliest discussions. Second arily, I have tried to give some clues as to the influence this early material may have had in forming the image of the "good" Bish op that emerged in the second half of the eighteenth century. For it is my hope that such clues may prove helpful in freeing us from the more severe strictures of the traditional interpretive dogmas.